2019
DOI: 10.1049/iet-nbt.2018.5408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of negative functionalisation of gold nanorods on conformation and activity of human serum albumin

Abstract: The theranostic applications of gold nanorods (AuNRs) are limited due to the presence of cytotoxic cetrimonium bromide (CTAB) stabiliser, leading to the instigation of alternate stabilisers like negatively charged polystyrene sulphonate (PSS). Despite previous reports suggesting the impact of PSS-AuNRs on cells, their effect on the most abundant protein in plasma, i.e. human serum albumin (HSA), has not been studied before. Hence, the impact of PSS-AuNRs on HSA was thoroughly examined using varied spectroscopi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…red 2G (1) 0.0, (2) 0.2, (3) 0.4, (4) 0.6, (5 These results indicated that the microenvironment around the amino acid residues in HGG remains unchanged upon the interaction with R2G and a lack of significant conformational changes in the protein structure [14]. An increase in the absorbance of HGG is due to the formation of a ground-state combination between red 2G and HGG [15]. The Benesi-Hildebrand (B-H) plot was formed using the changes in absorbance intensity of HGG in the presence of R2G.…”
Section: Resultsmentioning
confidence: 91%
“…red 2G (1) 0.0, (2) 0.2, (3) 0.4, (4) 0.6, (5 These results indicated that the microenvironment around the amino acid residues in HGG remains unchanged upon the interaction with R2G and a lack of significant conformational changes in the protein structure [14]. An increase in the absorbance of HGG is due to the formation of a ground-state combination between red 2G and HGG [15]. The Benesi-Hildebrand (B-H) plot was formed using the changes in absorbance intensity of HGG in the presence of R2G.…”
Section: Resultsmentioning
confidence: 91%
“…Further, the surface charge of positively charged gold nanorods was modified into a negative charge by poly­(sodium 4-styrene sulfonate) (PSS). , The polyelectrolyte coating renders biocompatibility and stability to GNRs for various applications. , The excitation spectra of PSS-CTAB@GNRs showed a blue shift after the electrolyte coating (SI, Figure e). The FTIR analysis confirmed the existence of a sharp peak at 1500 cm –1 , confirming the presence of C–C stretching vibrations of PSS.…”
Section: Resultsmentioning
confidence: 99%